Adult temperament styles: a network analysis of their relationships with the Big Five Personality Model (European Journal of Education and Psychology, 2018)
This study investigated the connectivity structure among temperament styles and Big Five personality factors using network analysis. The temporal stability of temperament styles was also investigated. This study utilized two samples of Brazilian participants, the first for the network analysis and the second to investigate the stability of temperament styles. The first sample consists of 149 adults (57% women) ages 18 to 66 (M=32; SD=9.92), the second of 88 individuals (56% women) ranging from 18 to 41 years-of-age (M=23; SD=5.79). Results confirmed that temperament styles measured by the Inventory of Adult Temperament Styles formed networks with personality factors measured by the BFP. Community analysis indicated the presence of four clusters. Estimates of test-retest reliability were statistically significant. In conclusion, temperament styles are stable and can be conceived as a network of traits associated with personality.